Avaliação de lesões brancas de cáries: um estudo de prognóstico - Mendes, Neusa Sales (2011)
Objective: The aim of the present study is to assess the current situation of white enamel lesions on vestibular surfaces of permanent upper incisors, diagnosed 6 years ago, without clinical intervention. Methods: A prospective study reassessed 53 students of both sexes, aged between 13 and 18 years old, all attending the public school system in Natal, Brazil. Data collection was performed by duly calibrated examiners, and a clinical chart consisting of demographic data on dental caries, oral hygiene, and gingival condition was prepared. A tactile-visual examination was conducted using a clinical mirror and periodontal probe. Data compilation and analysis were carried out using a SPSS software. In this analysis the chi-squared test was used for qualitative independent variables. To identify the net effect of treatment, multiple logistic analysis with forward stepwise model selection was performed. Results: The final sample was composed of 106 lesions in the 53 individuals, with mean age of 15.02 years, visible plaque index (VPI) of 23.34%, and gingival blood indices (GBI) of 25.92%. A statistically significant relationship (p = 0.003) was found between initial DMFS and prognosis of white enamel lesion. Conclusions: We observed that past caries experience and dental plaque were the main predictive factors for negative lesion outcomes, demonstrating the need for oral hygiene control through continuing preventive measures